2019
DOI: 10.1002/prep.201900245
|View full text |Cite
|
Sign up to set email alerts
|

Application and Properties of CL‐20/HMX Cocrystal in Composite Modified Double Base Propellants

Abstract: The composite modified double base (CMDB) propellants containing 2,4,6,8,10,12‐hexanitro‐2,4,6,8,10,12‐hexaazatetracyclo[5.5.0.05,9.03,11] dodecane (CL‐20), 1,3,5,7‐tetranitro‐1,3,5,7‐tetrazocane (HMX) or CL‐20/HMX cocrystal were prepared by the solventless extrusion formation technique. The performances of CMDB propellants were evaluated by means of stability, sensitivity, combustion and mechanical experiments. Raman spectra analysis indicated the stability of CL‐20/HMX cocrystal is partially destroyed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“… 1 In order to improve its energy performance to achieve a higher destructive effect, the main approach is through the addition of a high-energy solid explosive. 2 CL-20 (hexanitrohexaazaisowurtzitane) is one of the most attractive high energy density compound with promising applications in the fields of propellants and explosives. 3 It is expected to improve the specific impulse, detonation pressure, and detonation velocity properties of munitions owing to its unique highly strained molecular cage structure.…”
Section: Introductionmentioning
confidence: 99%
“… 1 In order to improve its energy performance to achieve a higher destructive effect, the main approach is through the addition of a high-energy solid explosive. 2 CL-20 (hexanitrohexaazaisowurtzitane) is one of the most attractive high energy density compound with promising applications in the fields of propellants and explosives. 3 It is expected to improve the specific impulse, detonation pressure, and detonation velocity properties of munitions owing to its unique highly strained molecular cage structure.…”
Section: Introductionmentioning
confidence: 99%
“…23b The Navy has produced DINA on large scales for flashless gun propellant, and more recent work has demonstrated that DINA can be employed successfully in CL-20- and HMX-based double-base rocket propellants. 24 …”
Section: Nitric Ester Propellantsmentioning
confidence: 99%
“…CL-20 excels compared to the other high-energy explosive materials such as HMX, RDX, PETN, etc. CL-20 is viewed as a potential component of solid propellants [ 22 , 23 , 24 , 25 , 26 , 27 ] and composite explosives [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Despite the merits of CL-20, its wide application is hindered by its high manufacturing cost.…”
Section: Introductionmentioning
confidence: 99%